Orthopedic Surgery Triggers Attention Deficits in a Delirium-Like Mouse Model - Velagapudi, Ravikanth; Subramaniyan, Saraswathi; Xiong, Chao; Porkka, Fiona; Rodriguiz, Ramona M.; Wetsel, William C.; Terrando, Niccolò (Frontiers in Immunology, 2019)
Postoperative delirium is a frequent and debilitating complication, especially amongst high risk procedures such as orthopedic surgery, and its pathogenesis remains unclear. Inattention is often reported in the clinical diagnosis of delirium, however limited attempts have been made to study this cognitive domain in preclinical models. Here we implemented the 5-choice serial reaction time task (5-CSRTT) to evaluate attention in a clinically relevant mouse model following orthopedic surgery. The 5-CSRTT showed a time-dependent impairment in the number of responses made by the mice acutely after orthopedic surgery, with maximum impairment at 24 hours and returning to pre-surgical performance by day 5. Similarly, the latency to the response was also delayed during this time period but returned to pre-surgical levels within several days. While correct responses decreased following surgery, the accuracy of the response (e.g., selection of the correct nose-poke) remained relatively unchanged. In a separate cohort we evaluated neuroinflammation and blood-brain barrier dysfunction using clarified brain tissue with light-sheet microscopy. CLARITY revealed significant changes in microglial morphology and impaired astrocytic-tight junction interactions using high-resolution 3D reconstructions of the neurovascular unit. Deposition of IgG, fibrinogen, and autophagy markers (TFEB and LAMP1) were also altered in the hippocampus 24 hours after surgery. Together, these results provide translational evidence for the role of peripheral surgery contributing to delirium-like behavior and disrupted neuroimmunity in adult mice.